ESTIMATION OF DATA TRAFFIC OVERLOAD FOR SATELLITE COMMUNICATIONS - Bo, Wang; Kharchenko, Volodymyr; Grekhov, Andrii; Ali, Ismail (Proceedings of National Aviation University (archive), 2016)
For modelling of aviation data transmition with the help of low-orbit satellites different models of communication channel "Aircraft-Satellites-Ground Station" were built using NetCracker Professіonal 4.1 software. Influence of aircraft and satellites amount on average downlink utilization and message travelling time was studied for telecommunication channels with intersatellite link. The effect of communication channel overload during simultaneous data transmission through several satellites from many aircraft was investigated.